A 2005 social accounting matrix for Burkina Faso - Balma, Lacina; Bako, Dramane; Kaboré, Barbi (International Food Policy Research Institute, 2015)
The 2005 Social Accounting Matrix (SAM) for Burkina Faso is an agricultural-focused SAM and, as such, it is mainly elaborated from the Agricultural Supply and Use Table (ASUT) for the same year. The matrix is then complemented with other sources of data including the 2005 National Supply and Use Table (NSUT), the 2005 Integrated Economic Accounts Table (IEAT), 2003 household survey data, and 2006-08 agricultural survey data. The SAM subsequently presents in its detailed structure 132 accounts of goods and services, of which 47 are agricultural products, and 74 accounts of activities. The factor account consists of three categories of agricultural workers and two types of capital, distinguishing between agricultural and non-agricultural capital. The accounts for the institutional units distinguish between four representative categories of households, one Government account, two accounts of financial and non-financial corporations, and one account of non-resident institutions or Rest of the world (ROW).